Endogenous competition exposure: China's rise, intra-industry and intra-firm reallocations - Benjamin Gampfer; Ingo Geishecker (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper we analyse the manufacturing sector's capacity to mitigate increasing import competition from China. In our view, competition exposure is endogenous, i.e. influenced by firms' decisions which products are sold and what markets are served. We construct a counterfactual competition measure to assess the importance of different types of adaptation to increased competition: inter- and intra-industry reallocations, firm entry and exit, and product- and destination switching, among others. Combining Danish firm register data with transactional level trade statistics we are able to track product-level competition changes on the domestic as well as on each export market. Between 1997 and 2008 aggregated manufacturing level exposure to Chinese imports increased by 177 per cent but counterfactually would have increased by remarkable 283 per cent had the manufacturing sector not successfully adapted. The mitigation of sector level competition exposure works through all adaptation channels, notably firm entry and exit, and inter-industry reallocations. However, for surviving firms, product and destination switching are very relevant mechanisms to mitigate increased competitive pressure from China.
Keywords: F14; F60; L60; 330